Tarptautinis bibliotekų bendradarbiavimas - Macevičiūtė, Elena (Knygotyra, 1983)
In 1853 American librarians and publishers had organized a conference. The librarians of various countries took part in it. The report about this conference was published in Ch. Norton’s “Literary and Educational Register for 1854”. This was the beginning of official history of the international library cooperation. The main periods of the development of the international library cooperation are given and characterized in the article. The author gives the definition of the international library cooperation. It is defined as the activities stimulated by the processes going on in society and carried out by the governmental and non-governmental institutions and organizations, groups of persons and separate persons for organization, development and evaluation of library and information services.